Sport Monopoly Games: A Physical Education Learning For Physical Fitness Student - Hambali, Sumbara; Hardi, Veny Juniarni; Supriyatni, Deswinta; Pristiawati, Ani; Verianti, Giri; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
Fitness is still an important study in life. The study of physical fitness is still a problem that seems to be currently a polemic among elementary school students. This happens because of a shift in physical activity habits in student life. The purpose of this study was to find out an overview of the impact of a Sport Monopoly Games (SMG) game on students' physical fitness. A total of 105 students spread across the Cimahi City, Indonesia area participated in this research, namely schools in the northern, central and southern regions. The research method uses experiments with research design one shoot case study. The instrument uses a measuring instrument in the form of the Indonesian Student Fitness Test (TKSI) Phase C, which consists of five test items: 1) Child Ball; 2) Tok Tok Ball; 3) Shuttle Run 4x10 m Get ball; 4) Move the Ball; 5) Run 600 m. The data analysis used a percentage approach, and using the tools of Ms Excel 2019 and IBM SPSS version 26 programs. Average physical fitness score from the northern region is greater at 15.6 than the other two regions, namely the central region 15.4 and the southern region 14.9. However, if you look at the TKSI value category table, the three regions on average have the same fitness level, which is in the medium category. The results of the study found that the average student had a moderate level of physical fitness after being given treatment using SMG. Physical education teachers can apply this game in physical fitness materials at school, so that the learning process is not monotonous and a little challenging for students.